pengaruh Pengaruh Aglomerasi Industri, Upah Minimum Provinsi, Dan Jumlah Angkatan Kerja Terhadap Pendapatan Asli Daerah Se-Pulau Sumatera Dalam Perspektif Ekonomi Islam (Analisis Data Panel Tahun 2018-2024): (Analisis Data Panel Tahun 2018-2024) - Putri, Putri Amalia; Noviarita, Heni; Setyanto, Alief Rakhman (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2025)
Local Own-Source Revenue (PAD) is an indicator of fiscal independence and the success of regional development. On the island of Sumatra, PAD values vary between provinces, influenced by industrial agglomeration, minimum wage policies, and the size of the labor force. This study aims to analyze the influence of these three factors, namely industrial agglomeration, provincial minimum wages, and the size of the labor force, on PAD in ten provinces on the island of Sumatra for the period 2018-2024 using a quantitative approach based on panel data analysis using Common Effect, Fixed Effect, and Random Effect models. The results show that industrial agglomeration does not have a significant effect on PAD, while provincial minimum wages and the size of the labor force have a significant positive effect, and simultaneously, all three contribute significantly to the increase in PAD. These findings confirm that strengthening PAD is more determined by fair wage policies and the utilization of productive labor than by industrial concentration. From an Islamic economic perspective, these research results are in line with the principles of justice, balance, and maslahah, which emphasize the equitable distribution of economic benefits. This study contributes academically to the regional economic literature and provides practical recommendations for local governments in formulating sustainable fiscal strategies